Effect of Worn Top Compression Ring and Lubricant Degradation Towards Engine In-Cylinder Frictional Losses - Nur Aisya Affrina, Mohamed Ariffin; Tan, Jia Yii; Lee, Chiew Tin; William Chong, Woei Fong (Penerbit UTM Press, 2025)
Friction occurs in the internal combustion engine especially at the interface between piston ring and cylinder liner. This causes an increase in fuel consumption required to overcome these frictional losses. Piston ringcylinder interface is one of the primary sources. This study is imperative to understand the effects of lubrication degradation and worn top compression ring towards engine frictional losses. A mathematical model with the integration of 1-D Reynold’s equation is derived to investigate the lubrication film and pressure generation. This study further incorporates velocity, surface roughness, combustion pressure, lubrication degradation and presence of worn top compression ring to demonstrate the frictional losses. It was found that lubrication degradation significantly affects the lubrication film formation, impacting friction at the piston ring-cylinder liner interface. Increased lubricant viscosity increases viscous friction while reducing boundary friction. Similarly, a worn top compression ring leads to higher viscous friction due to a thicker film and larger load-bearing area, decreasing boundary friction. It is concluded that both lubrication degradation and worn top compression rings have detrimental effects on frictional power losses